Assessment of thyroid functions and thyroid volume in normal pregnant Egyptian females. (1st February 2020) - Elebrashy, Ibrahim; Kamal Eldein, Hebat-Allah; Abd-Elstar, Hoda; Ghanem, Nashwa; Mousa, Shrook; Assem, Maha; Rashed, Laila; Salit, Mohamed; Abd-Elraoof, Maged; Dorgham, Ahmed; Mansour, Ahmed; Mahmoud, Mohamed; et al.
Abstract: The normal range of thyroid functions during pregnancy differs between ethnic groups. This study assessed the thyroid functions in normal pregnant Egyptian females. Thyroid peroxidase antibodies (TPO Abs) and thyroid volume were also assessed. The study included 150 normal pregnant Egyptian females, recruited from Cairo University Hospital Antenatal Care Clinic (50 in each trimester), with 40 age-matched non-pregnant females, as a control group. Serum thyroid stimulating hormone (TSH) and TPO Abs were measured. Thyroid volume was assessed by ultrasonography. TSH ranges were 0.21–1.7, 0.52–3.2 and 0.72–2.6 mIU/L during first, second and third trimesters, respectively. The mean TSH level in pregnant females was significantly lower than that of non-pregnant women (1.2 ± 0.7 vs 2.7 ± 0.9 mIU/L, p < .001). TPO Abs were significantly higher in the first trimester compared to both second and third trimesters ( p < .001 for both). Thyroid volume of pregnant females was non-significantly higher than that of non-pregnant control subjects ( p = .126). A significant positive correlation was found between thyroid volume and body mass index in pregnant females ( p < 0.001). Our study established trimester-specific reference ranges for thyroid functions in normal pregnant Egyptian females. A larger population-based study would help to confirm those ranges. Thyroid volume was non-significantly higher than that of non-pregnant control subjects.